Artemisia halodendron Litters Have Strong Negative Allelopathic Effects on Earlier Successional Plants in a Semi-Arid Sandy Dune Region in China - Luo, Yongqing; Du, Zhong; Yan, Zhiqiang; Zhao, Xueyong; Li, Yuqiang; Jiang, Haibo; Yang, Yue; Li, Mai-He (Frontiers in Plant Science, 2020)
Artemisia halodendron Turcz. ex Besser occurs following the appearance of a pioneer species, Agriophyllum squarrosum (L.) Moq., with the former replacing the latter during the naturally vegetation succession in sandy dune regions in China. A previous study revealed that the foliage litter of A. halodendron had strong negative allelopathic effects on germination of the soil seed bank and on the seedling growth. However, whether this allelopathic effect varies with litter types and with the identity of plant species has not yet been studied. We, therefore, carried out a seed germination experiment to determine the allelopathic effects of three ltter types of A. halodendron (roots, foliage, and stems) on seed germination of six plant species that progressively occur along a successional gradient in the semi-arid grasslands in the Horqin Sandy Land of northeastern China. In line with our expectation, we found that the early-successional species rather than the late-successional species were negatively affected by A. halodendron and that the allelopathic effects on seed germination increase with increasing concentration of litter extracts, irrespective of litter types. Our study evidenced the negative allelopathic effects of A. halodendron on the species replacement and on the community composition during dune stabilization in the Horqin Sandy Land. Further studies are needed to better understand the successional process and thus to promote the vegetation restoration in that sandy dune region as A. halodendron itself disappeared also during the process.